Analysis of Social Change in Legal Development in Indonesia - Meutia ainul hakim; Giyosi Giyosi; Desy Fitriani; Diky Dikrurahman; Deni Yusup Permana (International Journal Labs, 2024)
All aspects of community life, whether political, social, cultural, or economic, are regulated by law. Therefore, the existence of this law is universal. Development and reform give rise to social changes that give rise to social problems, which puts pressure on the law because the law must be able to overcome these problems. The aim of this research is to analyze social changes in the development of law in Indonesia. This research uses a statutory approach, also called a statutory approach. The results of this research show that law and social change have a close interaction in the context of social change. Both have an impact on each other. Changes in law are influenced by changes in society, and vice versa. Social transformation in society is influenced by legal changes as well. Based on the analysis that has been carried out, social changes in the development of law in Indonesia are: 1) Law Number 11 of 2008 was born, which regulates electronic information and transactions. Law plays two important roles in social change: law as a tool of social control and a technique of social engineering; 2) institutions have an important role in society; the existence of Rukun Warga (RW) and Rukun Tetangga (RT) officials as well as Village Government institutions is also crucial. The role of the village government and RT-RW can be utilized to empower the community effectively in carrying out prevention. 3) Providing legal understanding refers to awareness of the rules established by written law for behavior, namely what the community can and cannot do.